Novel nitric oxide donors for the dispersal and control of Pseudomonas aeruginosa biofilms - Poh, Wee Han (2018)
The use of nitric oxide (NO) represents a novel strategy for the control of biofilms by inducing biofilm dispersal and promoting the eradication of susceptible, dispersed cells by antibiotic treatment. NO, as a free radical, is highly reactive and its production and metabolism is tightly regulated under physiological conditions. In addition, due to the involvement of NO in various pathological processes, several classes of NO donors with varying pharmacological properties have been developed for different treatments. In the case of biofilm control, two main classes of NO donor are typically used to induce biofilm dispersal, sodium nitroprusside (SNP) and diazeniumdiolates (NONOates). The latter of which generally have short half-lives. In the first study, an alternative class of NO donors, furoxans, which can have an extended duration of NO-release, was evaluated as a biofilm dispersing agent using P. aeruginosa biofilms. It was shown that a furoxan with a shorter half-life, LL4254, could induce dispersal to a similar extent as a control NONOate. Furoxans with longer half-lives, LL4212 and LL4216, could also induce biofilm dispersal, but only when used at higher concentrations. As LL4212 and LL4216 were later found to affect the growth of P. aeruginosa, they were considered unsuitable for use as biofilm dispersing agents. Thus, the study indicated that secondary effects of NO donor compounds were important considerations for their development as biofilm control agents. In the second study, the application of cephalosporin-linked diazeniumdiolate NO donors, which are stable until activation by bacterial specific β-lactamases present within biofilms, were evaluated. The study laid the groundwork for the assessment of these compounds in vivo, as factors influencing NO release from these compounds were evaluated. While the compounds were effective in dispersing P. aeruginosa biofilms in vitro, their activity was limited in vivo, likely due to differences in experimental conditions in the two systems. Preliminary assessment of one lead compound, DEACP, in a mouse implant model of biofilm infection also suggested that dispersal may lead to poor prognosis, as higher bacterial counts were retrieved from spleen samples of mice in NO-treated groups as a consequence of dispersal. Further studies would be required for optimization of the use of these compounds in vivo. In addition, antibiotic treatment is recommended for clearance of dispersed bacteria to reduce incidences of sepsis due to dispersed cells. In the last study, genes and proteins that may be involved in NO sensing and NO induced dispersal were tested for their response to NO treatment. Two purified proteins, DipA and RbdA, were not found to act as sensors of NO, and are likely to be involved in the dispersal process through other mechanisms. Using a batch microplate system for biofilm dispersal, transposon mutants of several genes previously shown to be defective in dispersal in flow systems, were unexpectedly found to be unaffected in NO induced dispersal, indicating that there may be genetic redundancies and that the response to NO and that NO induced dispersal may be additionally regulated by the growth conditions.